Evaluation of glucose and sucrose osmotic dehydrated and heat-air-dried Flordarking peach slices during conservation - Salvañal, Lara; Gabilondo, Julieta; Francesconi, Rafaela; Budde, Claudio Olaf; Pieroni, Victoria; Gugole Ottaviano, María Fernanda; Sosa, Miriam; Andres, Silvina; Garitta, Lorena Verónica; Lara, María Valeria; Corbino, Graciela Beatriz (Asociación Argentina de Tecnólogos Alimentarios (AATA), 2023)
Poster